Subabul based feed pellets as strategic supplements for goats - Mahanta, S K; Sharma, Purushottam; Kumar, Sunil; Choudhary, Mukesh; Dwivedi, R P; Manjunath, N; Upadhayay, J P; Chandra, Avinash; Saxena, A K; Gupta, Rajeev; Singh, Upendra; Kumar, Prashant (Indian Farming, 2021)
In Bundelkand region, livelihood security is highly vulnerable. Livestock, particularly goat farming is an important source of livelihood contributing to household income, employment and nutritional security. However, the potential for goat production is limited by many environmental and nutritional factors, and supplementation is required to mitigate both, nutrient deficiencies and the effect of plant secondary metabolites. Strategic supplementation option with complete feed pellets (consist of wheat straw, subabul leaf meal, wheat bran, mustard cake, barley grain and mineral mixture) can serve as good protein and energy sources for goats. On-farm trials with goat, farmers indicated that providing complete feed pellets as a strategic supplement (@ 200g/head/ day or around 1.0% of the body weight) to growing goats, reared on exclusive grazing, increased body weight gain (by 1.27 times) as well as farm income.